The Medawar Lecture 1998 Is science dangerous? - Wolpert, Lewis (The Royal Society, 2005)
The idea that science is dangerous is deeply embedded in our culture, particularly in literature, yet science provides the best way of understanding the world. Science is not the same as technology. In contrast to technology, reliable scientific knowledge is value-free and has no moral or ethical value. Scientists are not responsible for the technological applications of science; the very nature of science is that it is not possible to predict what will be discovered or how these discoveries could be applied. The obligation of scientists is to make public both any social implications of their work and its technological applications. A rare case of immoral science was eugenics. The image of Frankenstein has been turned by the media into genetic pornography, but neither cloning nor stem cells or gene therapy raise new ethical issues. There are no areas of research that are so socially sensitive that research into them should be proscribed. We have to rely on the many institutions of a democratic society: parliament, a free and vigorous press, affected groups and the scientists themselves. That is why programmes for the public understanding of science are so important. Alas, we still do not know how best to do this.